A new measure of the Canadian effective exchange rate - Russell Barnett; Karyne Charbonneau; Guillaume Poulin-Bellisle (Bank of Canada, 2016)
Canada's international competitiveness has received increasing attention in recent years as exports have fallen short of expectations and Canada has lost market share. This paper asks whether the Bank of Canada's current effective exchange rate measure, the CERI, is still an accurate measure of Canada's international competitiveness. Overall, while the CERI represented an improvement over previous measures when it was introduced, we find that it has several drawbacks that make it less well suited to address current competitiveness issues. To address these deficiencies, we develop a new Canadian effective exchange rate (CEER) index using a methodology based on current international best practices. The new index includes a broader set of countries and uses annually updated competition-based weights. These weights account for both Canada's bilateral trade with another country and the competition Canada faces from that country on a product-by-product basis in third markets. We find that the CEER has depreciated less than the CERI in recent years, reflecting the greater importance of third-market competition from emerging-market economies in the CEER. This could help explain why Canada's share of the U.S. import market has continued to decline despite the recent large depreciation of the Canadian dollar against the currencies of a number of advanced economies.
Keywords: F; F1; F3; F31; 330; Exchange rates; International topics